РОСТОВЫЕ И БИОХИМИЧЕСКИЕ ХАРАКТЕРИСТИКИ SPIRULINA (ARTHROSPIRA) PLATENSIS (NORDST.) GEITLER ПРИ РАЗЛИЧНЫХ УСЛОВИЯХ АЗОТНОГО ПИТАНИЯ - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2002)
Исследовано влияние различных концентраций нитрата натрия в среде Заррука на рост и химический состав Spirulina (Arthrospira) platensis при ее выращивании в культиваторах открытого типа в квазинепрерывном режиме. Показана положительная корреляция между уровнем азота в среде, с одной стороны, и продуктивностью культуры, содержанием белка и пигментов фотосинтетического комплекса, с другой.
Growth and biochemical characteristics of Spirulina platensis (Nordst.) Geitler under different conditions of nitrogen nutrition
The influence of different medium nitrate concentrations on the growth and chemical composition (the content of protein, chlorophyll a, C-phycocyanin and total carotenoids) of S. platensis at industrial semicontinuous cultivation was investigated. Medium nitrate content reduction in the range from 500 to 100 mg N/l had no effect on algal productivity at exponential growth stage. But for all that the percentage of protein and photosynthetic pigments (most important metabolites determining a physiological state of culture) in biomass decreased significantly. Protein and pigments content values were the lowest at 30-10 mg N/l, when normal functioning of metabolic cycles was limited. Such N concentrations seem to be close to the lower nitrogen tolerance limit for spirulina at the specified cultivation method. Nevertheless culture was in a viable state even in these conditions due to high adaptation potential of this species.